Upcycling orange waste into porous carriers for organic phase-change materials - Possari, Laís Taguchi (2025)
This thesis investigates the upcycling of orange juice waste biomass into aerogels and cryogels, and their performance as organic carriers of phase-change materials (PCMs). PCMs can store and release thermal energy at nearly constant temperatures during phase transitions, typically solid–liquid, which makes them suitable for passive temperature regulation applications. Aqueous suspensions were prepared by subjecting the whole and fractionated biomass waste (namely peels, pulp, and bagasse) to a citric acid pre-treatment, which promoted the extraction and solubilization of pectin into the liquid phase, and the swelling and fibrillation of the insoluble fraction. The kinetic stability of suspensions was tuned by adjusting preparation parameters (e.g., washing or non-washing, biomass and citric acid contents), enabling the production of homogeneous 3D porous materials using different processing routes. Aerogels were prepared via non-solvent-induced phase separation (with ethanol or acetone) followed by drying with supercritical carbon dioxide, and cryogels via suspension freezing followed by lyophilization. Aerogel beads were also produced by dripping the biomass suspension in ethanol prior to supercritical drying. Porous materials with varied morphologies, textural and mechanical properties, thermal conductivities and biodegradation rates in seawater were obtained. Two organic PCMs, polyethylene glycol and coconut oil, were loaded into obtained porous materials via vacuum-assisted melt impregnation for dimensional stabilization. The resulting phase-change composites were characterized for their thermal behavior and leakage resistance above the PCMs melting temperature, showing that the porous materials’ morphology and compatibility with the PCMs had a decisive impact on their performance as carriers for PCMs.